(NfILOSOFIQ MIRA PROTIW IDEOLOGII WOJNY (B/s - (N~ALDYMOW(B, (Nn(B.(Na(B.s ((NmOSKWA (B:s (NmYSLX(B,s, 1988)
(NbIBLIOGR(B. (NW PRIME^(B.: (NS(B. 296-313s
Keywords: (NbORXBA ZA MIRs; (NwOJNAs; (NmIRNOE SOSU]ESTWOWANIEs